2001
DOI: 10.1152/jn.2001.85.5.1836
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity Induced by Tooth Pulp Stimulation in Trigeminal Subnucleus Oralis Involves NMDA Receptor Mechanisms

Abstract: We have recently demonstrated that application of the mustard oil (MO), a small-fiber excitant and inflammatory irritant, to the rat maxillary molar tooth pulp induces significant increases in jaw muscle electromyographic (EMG) activity and neuroplastic changes in trigeminal (V) subnucleus caudalis. Since subnucleus oralis (Vo) as well as caudalis receives projections from molar pulp afferents and is also an integral brain stem relay of afferent input from orofacial structures, we tested whether MO application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 77 publications
3
18
0
Order By: Relevance
“…Intersubnuclear communication in trigeminal sensory processing has been examined from various forms of input including facial skin (Dallel et al, 1998;Greenwood and Sessle, 1976;Woda et al, 2001), tooth pulp Hu et al, 2002;Park et al, 2001), ocular surface (Hirata et al, 2003(Hirata et al, , 2004 and dural membranes (Davis and Dostrovsky, 1988). In addition, it has been suggested that central axons of neurons innervating tooth pulp terminate heavier to Vo than Vc (Arvidsson and Gobel, 1981;Marfurt and Turner, 1984;Shigenaga et al, 1986;Takemura et al, 1991Takemura et al, , 1993, and those innervating facial areas primarily to the Vc (Takemura et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intersubnuclear communication in trigeminal sensory processing has been examined from various forms of input including facial skin (Dallel et al, 1998;Greenwood and Sessle, 1976;Woda et al, 2001), tooth pulp Hu et al, 2002;Park et al, 2001), ocular surface (Hirata et al, 2003(Hirata et al, , 2004 and dural membranes (Davis and Dostrovsky, 1988). In addition, it has been suggested that central axons of neurons innervating tooth pulp terminate heavier to Vo than Vc (Arvidsson and Gobel, 1981;Marfurt and Turner, 1984;Shigenaga et al, 1986;Takemura et al, 1991Takemura et al, , 1993, and those innervating facial areas primarily to the Vc (Takemura et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anatomical (Voisin et al, 2002) or functional Dallel et al, 1998;Hu et al, 1981;Park et al, 2001;Woda et al, 2001) studies have recently demonstrated an ascending connection from Vc to Vo which may be required for C-fiber-mediated nociceptive transmission from Vc to Vo (Pajot et al, 2000). In spite of these studies above, pharmacological analysis of the intersubnuclear synaptic transmission have not been tried yet.…”
Section: Introductionmentioning
confidence: 99%
“…The average spontaneous activity in hertz of a nociceptive neuron was determined over the initial 1 min (for NS neurons) or 5 min (for WDR neurons) recording period. As outlined in our previous studies (Chiang et al, 1998(Chiang et al, , 2005Park et al, 2001;Hu et al, 2002;Xie et al, 2007), the cutaneous mechanoreceptive field (RF) of each WDR neuron was determined by brushing the skin with a force Ͻ2 g; the cutaneous pinch/pressure RF of each NS or WDR neuron was determined through the use of a blunt probe and a pair of nonserrated forceps. A burst response consisting of at least two spikes during each stimulus trial was accepted as the criterion for the RF boundary of the neuron tested.…”
Section: Methodsmentioning
confidence: 99%
“…For NS neurons, the activation threshold to a mechanical stimulus applied to the orofacial RF was assessed by a pair of forcemonitoring forceps (with an attached strain gauge that monitored force levels up to 600 g/mm 2 ) or an electronic von Frey monofilament, and as the mechanical force was gradually increased, the responses of the tested neuron were monitored and recorded simultaneously by the use of the Spike2 program (CED 1401 plus). The NS neuronal responses to four incremental graded mechanical pinch stimuli with a force-monitoring forceps or graded pressure by means of electronic von Frey monofilament applications (e.g., 20 -25, 40 -50, 60 -80, 100, and even 200 g, delivered in ascending order, each for 5 s at an interval of Ͼ45 s) applied to the neuronal orofacial RF were determined, as described previously (Chiang et al, 1998(Chiang et al, , 2005Park et al, 2001;Hu et al, 2002;Xie et al, 2007). The pinch/pressure-evoked responses of a given neuron were assessed by summing the number of spikes evoked by each of these four graded stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…Vsp comprises three subnuclei, that is, oralis (Vo), interpolais (Vi) and caudalis (Vc) in rostrocaudal direction [6], which are interconnected by excitatory and inhibitory synaptic transmission [7][8][9]. Of the intersubnuclear connections, an ascending transmission from Vc to Vo plays an important role in the orofacial nociceptive transmission in the trigeminal system [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%